2018
DOI: 10.1111/ajgw.12347
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a BrazilianTorulaspora delbrueckiiisolate and a commercialSaccharomyces cerevisiaeto the aroma profile and sensory characteristics of Moscato Branco wines

Abstract: Background and Aims Moscato Branco is the most important cultivar used in the production of Brazilian muscat sparkling wines and is responsible for their sensory characteristics. The aim of this work was to evaluate the effect of monoculture and co‐fermentations by Torulaspora delbrueckii (TPI‐4) and Saccharomyces cerevisiae (EC1118) on the physicochemical, aromatic composition and sensory characteristics of Moscato Branco wines. Methods and Results Wines inoculated with axenic and co‐inoculated with S. cerevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In addition, certain volatile compounds contributed by T. delbrueckii have been positively related to the fruity character of the wine. For instance, linalyl acetate, with citrus aroma descriptor, far exceeded its odour threshold (0.05 mg/L) in white Muscat fermentations by T. delbrueckii [40]. Similarly, sequential fermentation between T. delbrueckii and S. cerevisiae resulted in higher concentrations of 3-mercaptohexan-1-ol (grape fruit and passion fruit descriptors [42]) and its acetate (boxwood and passion fruit descriptors [43]) [41].…”
Section: Influence Of Non-saccharomyces Yeasts On Wine Aromamentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, certain volatile compounds contributed by T. delbrueckii have been positively related to the fruity character of the wine. For instance, linalyl acetate, with citrus aroma descriptor, far exceeded its odour threshold (0.05 mg/L) in white Muscat fermentations by T. delbrueckii [40]. Similarly, sequential fermentation between T. delbrueckii and S. cerevisiae resulted in higher concentrations of 3-mercaptohexan-1-ol (grape fruit and passion fruit descriptors [42]) and its acetate (boxwood and passion fruit descriptors [43]) [41].…”
Section: Influence Of Non-saccharomyces Yeasts On Wine Aromamentioning
confidence: 98%
“…Currently, Torulaspora delbrueckii is a non-Saccharomyces yeast with great oenological potential due to its good fermentation performance with low levels of ethanol, higher alcohols, volatile fatty acids and volatile acidity, and its notable contribution to the aromatic profile of the wine [6,40].…”
Section: Influence Of Non-saccharomyces Yeasts On Wine Aromamentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have investigated specific effects of non-Saccharomyces yeast on wine quality. The yeasts that were studied include Hanseniaspora uvarum [31,32], Hanseniaspora vineae [26,33], Torulaspora delbrueckii [34][35][36][37][38], M. pulcherrima [29,[39][40][41], Starmerella bacillaris [22,42], Schizosaccharomyces pombe [43,44], Schizosaccharomyces japonicus [16], Lachancea thermotolerans [29,40,45], Zygotorulaspora florentina [46], P. kluvyeri [22,47], and Zygosaccharomyces bailii [48,49].…”
Section: Non-saccharomyces Yeastsmentioning
confidence: 99%
“…Romani et al [16] studied the effect of S. japonicus and found that the sequential fermentation with S. cerevisiae enhanced wine complexity and aroma by increasing higher alcohols (isobutanol, amylic and isoamylic alcohols), acetate esters (isoamyl acetate, phenyl ethyl acetate) and alcohols (β-phenyl ethanol) above their threshold levels. The effect of co-inoculation of T. delbrueckii and S. cerevisiae on Moscato Branco sparkling wines found that wines produced from co-fermentation had higher concentrations of 2-phenyl ethanol, acetate and ethyl esters with fruity and flowery descriptors while a decrease in concentration of undesirable compounds such as volatile fatty acids occurred [38].…”
Section: Volatile Aroma Compoundsmentioning
confidence: 99%